GLP-1 Gene-Modified Human Umbilical Cord Mesenchymal Stem Cell Line Improves Blood Glucose Level in Type 2 Diabetic Mice - Ying Chang; Mingxin Dong; Yan Wang; Haotian Yu; Chengbiao Sun; Xin Jiang; Wei Chen; Xin Wang; Na Xu; Wensen Liu; Ningyi Jin (Stem Cells International)
Type 2 diabetes constitutes a serious threat to the health of patients, but there is currently no ideal treatment in the clinic. Glucagon-like peptide-1 and human umbilical cord mesenchymal stem cells have been confirmed to have antidiabetic effects, but both of them have certain defects in the process of antidiabetes, which cannot meet the need of clinical treatment. We hypothesized that human umbilical cord mesenchymal stem cells can be used as a vector to construct a novel cell line that expresses GLP-1 in vivo for a long time. And this cell strain results in lowering blood glucose in type 2 diabetic mice. The results showed that after 3 weeks of intramuscular injection of the new cell line, the fasting blood glucose of type 2 diabetic mice returned to the normal range, and the hypoglycemic effect was maintained within 3 weeks after putting an end to the drug. At the same time, during the administration, the mice lost weight, the food intake decreased, the half-life of GLP-1 in the body prolonged, the IR reduced, and the pancreatic function recovered. The results of this study indicate that the novel cell line can prolong the half-life of GLP-1 in vivo and effectively lower blood sugar, which is a feasible method to improve type 2 diabetes.